2007
DOI: 10.1007/s10886-007-9364-4
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific Variation Within the Genus Asclepias in Response to Herbivory by a Phloem-feeding Insect Herbivore

Abstract: Induced plant responses to leaf-chewing insects have been well studied, but considerably less is known about the effects of phloem-feedings insects on induction. In a set of laboratory experiments, we examined density-dependent induction by the milkweed-oleander aphid, Aphis nerii, of putative defenses in four milkweed species (Asclepias incarnata, Asclepias syriaca, Asclepias tuberosa, and Asclepias viridis). We hypothesized that high aphid density would lead to increased cardenolide expression in species wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 32 publications
4
52
0
Order By: Relevance
“…The induced responses are broadly defined as any modification in the plant following damage, including changes of toxic or antinutritional compounds, other physiological characteristics and morphological trait (Zehnder and Hunter 2007). Except toxic or autinutritional factor, such as phenolic (Kudo 2003) and cardenolide (Zehnder and Hunter 2007), some metabolic changes, such as plant protein (Inbar et al 1999), sugar (Liu et al 1998), respiration and photosynthesis (Chen et al 2003a, b), are clearly part of the repair process to injured plant tissue (Edwards and Wratten 1983). In previous cases, it was shown that insect stress not only caused the defoliation, but also affected the growth rate and nutrition uptake (Feng and He 1995;Kosola et al 2001;Masters 1995;Xia et al 1993;Zehnder and Hunter 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The induced responses are broadly defined as any modification in the plant following damage, including changes of toxic or antinutritional compounds, other physiological characteristics and morphological trait (Zehnder and Hunter 2007). Except toxic or autinutritional factor, such as phenolic (Kudo 2003) and cardenolide (Zehnder and Hunter 2007), some metabolic changes, such as plant protein (Inbar et al 1999), sugar (Liu et al 1998), respiration and photosynthesis (Chen et al 2003a, b), are clearly part of the repair process to injured plant tissue (Edwards and Wratten 1983). In previous cases, it was shown that insect stress not only caused the defoliation, but also affected the growth rate and nutrition uptake (Feng and He 1995;Kosola et al 2001;Masters 1995;Xia et al 1993;Zehnder and Hunter 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For a total of 15 replicates per treatment, six leaf disks were placed together in a vial containing 1ml of methanol and stored at −80°C prior to analysis. We measured the Bcardenolide dose^provided to caterpillars on leaf disks using methods described by Zehnder and Hunter (2007).…”
Section: Methodsmentioning
confidence: 99%
“…We assessed the cardenolides that herbivores sequestered following wellestablished methods (Zehnder and Hunter, 2007;. Aphids and caterpillars were ground for 3 min in methanol, sonicated for 1 h, and then centrifuged for 6 min.…”
Section: Analysis Of Herbivore Traitsmentioning
confidence: 99%
“…Using these models, we evaluated the effects of AMF inoculum availability on three measures of cardenolides sequestered by herbivores; total cardenolide concentration (sum of all cardenolide peaks), cardenolide diversity (using Shannon's index), and cardenolide polarity (relative representation of lipophilic cardenolides), calculated by summing the relative peak areas multiplied by each peaks' retention time (Rasmann and Agrawal, 2011;Sternberg et al, 2012). A greater diversity of cardenolides and more lipophilic cardenolides are considered more toxic than lower diversity or more polar mixes (Fordyce and Malcolm, 2000;Zehnder and Hunter, 2007;Sternberg et al, 2012). Because herbivores feeding upon A. incarnata rarely sequestered cardenolides (Table S1), they were excluded from all sequestration analyses.…”
Section: Data Analysesmentioning
confidence: 99%